Future psychologists’ dispositional predictors of psychological well-being under martial law - Zinoviia Stepanivna Karpenko; Arsen Romanovych Klympush (Insight: the psychological dimensions of society, 2023)
The dispositional determination of the person’s psychological well-being in the context of emergencies was the focus of the article’s empirical investigation and theoretical justification. The purpose of the study was to clarify how, under martial law, the Big Five traits and the elements of a person’s psychological well-being correlate to one another. Methods:testing using M. Klimanska & I. Haletska’s (2019)Ukrainian adaptation of the short, five-factor TIPI-UKR questionnaire, S. Karskanova’s (2011) adaptation of “Scale of psychological well-being” by К. Ryff; survey;as well as descriptive statistics, factor analyses, correlation analyses, and structural interpretation of the data. Results. The empirical study’s entire sample comprised 48 female first-year Psychology students (the first group), 40 of them (83.3%, the second group)were extremely severely affected by the full-scale Russian invasion. In contrast to the second group, where the correlation was weaker and insufficient, extroversion was generally found to have a strong positive relationship with all aspects of psychological well-being. Yet, among the members of the second group, the value of openness to new experiences and a slightly lower level of conscientiousness was increasing. The Big Five traits’ factor analysis demonstrated the existence of integral personal dispositions that accounted for64.55% of the variance in the factors affecting psychological well-being. Stability, which was a combination of conscientiousness, agreeableness, and emotional stability, was connected to an individual’s ability to transcend their own values, while plasticity, which was a combination of extroversion and openness to new experiences, was connected to the operational and instrumental equipment of the disposition. Conclusions. Extroversion and openness to new experiences(the general factor “plasticity”), which under the influence of chronic stress led to the structural restructuring of the individual’s adaptive resources, have been shown to be the most significant predictors of the psychological well-being of future psychologists in the conditions of martial law.